INCREASING THE RESISTANCE OF TEMPERATURE EFFECTS OF SULFUR-BASED CONCRETES - I.G‘.Axmedov; I.I.Umarov; J.D. Nuritdinov (Journal of new century innovations, 2023)
Abstract. The theoretical basis of sulfur concrete was studied in the article. A number of positive properties of sulfur concrete were studied, and the results of practical work on improving the fire resistance properties were studied.